A Comparison of Soybean Oil Methyl Ester and Diesel Sprays Behavior and Atomization Characteristics - Jasim , Noor Mohsin (Journal of Petroleum Research and Studies, 2017)
The present numerical study compares between spray characteristics of diesel and soybean oil methyl ester (SME biodiesel) under non-evaporating sprays. The spray structure of diesel and biodiesel fuel (soybean oil) in a common rail injection system are investigated and compared with that of available experimental data used image processing and atomization performance analysis. The proposed approach for the liquid phase, which based on the sprays’ statistical properties, is used to present the gas and liquid phases in an Eulerian-Eulerian approach. The main concept for this model is the possibility of describing a poly disperses spray by using moments of a drop number size distribution function. The main reason for less spray tip penetration in the (SME) comparing with diesel because a larger droplet diameters is the higher density, surface tension and viscosity of (SME). The fuel properties effect on the near nozzle structure is studied. The comparisons are referring that the spray drag, breakup and collision processes are promoted.